A produção de leite e o profissional veterinário na percepção de produtores de leite de Pedro Leopoldo - MG, 1999 - Iram da Silva Ferrao (2000)
In an epidemiologic study with emphasis on qualitative research, interviews were conducted with 32 dairy farmers in the municipality of Pedro Leopoldo - MG affiliated Agricultural Cooperative will of this council. We tried to draw a socio-economic profile and the perception that these producers have in relation to aspects that involve the process of milk production and the involvement of veterinary medicine in this context. A sampling of products occurred randomly and was divided into three categories small (53.12%), medium (28.13%) and large producers (18.75%). The latter are responsible for 67.17% of the volume of milk produced, while small producers (53.12%) yield 9.08% of milk volume, demonstrating the great inequality in the composition of the productive chain of the industry. According to 78% of the interviewed farmers, the price of milk is the main problem of the activity. In relation to the vet, this is perceived differently by producers as their production facilities. Small products perceive this as a professional interventionist point, while most large producers believe a more effective action of the veterinarian in the production process. This difference clearly an inadequacy of veterinary services to small producers. The expected this work to support future research to identify prospects for enhancing milk production and stimulating reflections on the role and training of veterinary professional committed to rural development